Makna Ritual Cheng Beng dan Ziarah Kubur: Studi Komparatif Antara Tradisi Tionghoa dan Islam di Labuhan Batu - Sharmila, Sharmila; Lubis, Dahlia (Sekolah Tinggi Teologi Injili dan Kejuruan (STTIK) Kupang, 2025)
This article examines the meaning of the Cheng Beng ritual in the Chinese-Buddhist tradition and the Grave Pilgrimage in Islamic teachings in Labuhanbatu Regency, North Sumatra. These two practices were chosen because they both represent a form of respect for ancestors, but come from different religious traditions. Cheng Beng is carried out through cleaning graves, burning prayer paper and offering food, while Pilgrimage to the Grave emphasizes prayer and contemplation of death without the element of material offerings. This study uses a qualitative approach with a phenomenological method to explore the experiences and meanings of ritual actors from both communities. The results of the study show that although there are fundamental differences in theological aspects and forms of practice, both have similar social values, such as respect for ancestors, strengthening family ties, and cleaning graves as a form of respect. These findings show that interfaith cultural practices have the potential to strengthen the values ​​of tolerance, social cohesion, and harmony between religious communities. Thus, understanding the meaning of religious rituals in a multicultural society such as Labuhanbatu is important to support an inclusive and harmonious social life.